A Conceptual Review of the Determinants of Employee Innovative Work Behavior - Ebrahim, Zarina Begum; Ismail, Irzan; Kassim, Erne Suzila (Information Management and Business Review, 2023)
The increasing prevalence of digitalization, competitive markets, quick environmental changes, and the imperative of organizational sustainability have necessitated business organizations to adopt innovative practices. Hence, all organizations must foster a culture of innovative work behavior among their employees to ensure the organization’s ongoing survival and advancement. Nonetheless, comprehensive studies that methodically scrutinize the different factors affecting IWB within a unified theoretical model are insufficient. This research is a literature review to find and analyze factors that influence innovative work behavior. The findings of the literature review or existing research indicate that psychological empowerment, employee engagement, self-efficacy, knowledge sharing, perceived organizational support, climate for innovation, HRM practices, and transformational leadership have consistently demonstrated strong associations with employee IWB in various studies. This study additionally proposes a novel conceptual framework that examines the interplay between psychological empowerment, employee engagement, self-efficacy, knowledge sharing, perceived organizational support, climate for innovation, HRM practices and transformational leadership, with a specific focus on their impact on IWB. This framework holds potential for future investigations conducted by other scholars.